Indirect evidence that maternal microchimerism in cord blood mediates a graft-versus-leukemia effect in cord blood transplantation - van Rood, Jon J. (National Academy of Sciences, 2012)
During pregnancy women can develop B- and T-cell immunity against the inherited paternal antigens (IPAs) of the fetus, such as HLA, peptides of minor histocompatibilty antigens, and possibly onco-fetal antigens. The biological and pathological role of these pregnancy-induced immunological events is only understood in part. However, anti-IPA immunity in the mother persists for many decades after delivery and may reduce relapse in offspring with leukemia after HLA-haploidentical transplantation of maternal hematopoietic stem cells (HSC). We hypothesized that maternal anti-IPA immune elements cross the placenta and might confer a potent graft-versus-leukemia effect when cord blood (CB) is used in unrelated HSC transplantation. In a retrospective study of single-unit CB recipients with all grafts provided by the New York Blood Center, we show that patients with acute myeloid or lymphoblastic leukemia (n = 845) who shared one or more HLA-A, -B, or -DRB1 antigens with their CB donor's IPAs had a significant decrease in leukemic relapse posttransplantation [hazard ratio (HR) = 0.38, P < 0.001] compared with those that did not. Remarkably, relapse reduction in patients receiving CB with one HLA mismatch (HR = 0.15, P < 0.001) was not associated with an increased risk of severe acute graft-versus-host disease (HR = 1.43, P = 0.730). Our findings may explain the unexpected low relapse rate after CB transplantation, open new avenues in the study of leukemic relapse after HSC transplantation (possibly of malignancies in general), and have practical implications for CB unit selection.